Conceptualising building information modelling for construction education - Olowa, Theophilus; Witt, Emlyn; Lill, Irene (Journal of Civil Engineering and Management, 2020)
Digitalisation of the construction industry is both driving changes in construction education to meet emerging industry needs and providing opportunities for new delivery approaches. Universities are responding to these challenges in diverse ways including in their use of Building Information Modelling for construction education (BfCE). This research is aimed at understanding the existing approaches to BfCE. A systematic literature review of BfCE in universities was carried out which identified 305 relevant articles including 44 specific cases of BfCE. These were qualitatively analysed and a Straussian Theory Model (STM) was adopted to understand the different BfCE approaches reported in the literature, the contextual and intervening conditions which give rise to them and their consequences in order to develop a conceptual framework which sets out the relationships between these and the digitalisation of the construction industry. This study provides construction educators with a descriptive typology that depicts all possible BfCE approaches and which could assist them in determining suitable approaches and to conceptualise new approaches for teaching students to use Building Information Modelling (BIM) and also for leveraging BIM to enhance their teaching of other topics.